162 Assessment of daily intake by beef heifers of sweet potato storage roots under competitive limit-feeding conditions. (29th July 2019) - Parish, Jane A; Rutherford, Cobie; Meyers, Stephen L; Shankle, Mark W
Abstract: Excess consumption of sweet potato storage roots (SWP) poses an acidosis risk to cattle that may be mitigated by limit-feeding strategies. Yet limit-feeding is often administered to achieve mean desired daily DMI in groups of cattle with little regard for DMI variation among individuals. The study objective was to assess variation in daily DMI of SWP by beef heifers in limit-fed, competitive feeding groups. Twenty-four 9- to 10-mo-old Bos taurus crossbred heifers were stratified by initial BW (261.9 ± 8.8 kg) to 4 paddocks (6 heifers/ paddock) and offered SWP (24.9% DM on an as-fed basis; 7.7% CP, 5.9% ADF and 80% TDN on a DM basis) supplementation daily at a rate of 3.4 kg DM/ paddock with ad libitum access to mixed-grass pasture. After a 7-d acclimation period in which all heifers were trained to use a GrowSafe system, daily SWP DMI was monitored for 39 days. Standard deviation estimates were calculated from DMI data and used to classify DMI into the following levels: low (2.0 kg, >0.5 SD). Half of the heifers (mean SWP DMI = 0.0 ± 0.02 kg) never consumed SWP at the high DMI level, but 42% of the heifers (mean SWP DMI = 1.1 ± 0.02 kg) consumed SWP at the high DMI level for at least 18 days over the study duration. No heifers consumed at the moderate DMI level more than 16 days during the trial. This suggests that DMI of individual cattle offered SWP in limit-fed groups often either exceeds by approximately 2-fold per animal mean values of SWP offered per group or is at or near zero. Additional research is needed to elucidate optimal group feeding strategies to achieve individual DMI targets among cattle offered SWP.